Association between dietary oxidative balance score and constipation: evidence from National Health and Nutrition Examination Survey - Shi, Zhangpeng; Wang, Dandan; Yu, Jiacheng; Zhou, Mengting; Du, Jiahao; Qin, Huanlong; Zhu, Huiyuan (Frontiers in Nutrition, 2025)
BackgroundNumerous researches have revealed a correlation between dietary factors and the development of constipation. This study aimed to investigate the association between dietary oxidative balance score (DOBS) and constipation.Materials and methodsA cross-sectional study was conducted by us based on the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2010 including 31,034 individuals who completed a constipation questionnaire. The DOBS was calculated based on 16 dietary factors, containing 14 antioxidants and two prooxidants. Multiple logistic regression and restricted cubic spline (RCS) analyses were employed to examine the correlation between DOBS and constipation. Meanwhile, propensity score matching (PSM) was chosen to eliminate the effect of confounding variables.ResultsA total of 11,019 participants were identified as constipation. After adjusting for potential confounding variables, multiple logistic regression analysis indicated that decreasing DOBS (OR = 0.977, 95% CI: 0.966–0.987, p < 0.001) was apparently associated with increased risk of constipation incidence. Notably, the occurrence of constipation increased with reduced level of DOBS, as compared to Q1 (Q2, OR = 0.820, 95% CI, 0.682–0.988, p = 0.037; Q3, OR = 0.797, 95% CI, 0.653–0.973, p = 0.026; Q4, OR = 0.648, 95% CI, 0.528–0.797, p < 0.001).ConclusionLow levels of DOBS were positively associated with the risk of constipation development, demonstrating that DOBS could be employed as a dietary indicator of constipation prevention.